A constitutive model of the dynamic shear modulus dependence on temperature, prestrain, dynamic strain amplitude and magnetic field for magneto-sensitive elastomer. (1st June 2021) - Lejon, Jonas; Wang, Bochao; Kari, Leif
Graphical abstract: Highlights: Magneto-sensitive (MS) elastomer mainly embraces rubber and magnetizable particles Magnetic field, temperature, prestrain and strain amplitude affect its modulus A model integrating the effect of these four kinds of dependences is developed The fitting ability reveals the model can predict the modulus of MS elastomer accurately It accelerates the application of MS elastomer in sound and vibration area Abstract: A constitutive model for the temperature, prestrain, dynamic strain amplitude and the magnetic field dependence of the dynamic shear modulus for a magneto-sensitive (MS) elastomer is developed. It is an augmentation of a model consisting of an elastic, fractional order derivative viscoelastic and a nonlinear amplitude-dependent smooth Coulomb friction model. The magnetic field dependence is reflected by a parabolic function with an upper limit. A Yeoh formulation of the strain energy function is applied to represent the prestrain dependence. To cover the temperature dependence, a Williams-Landel-Ferry function and an Arrhenius function are used. After parameter identification, a good agreement between the simulation and measurement results is shown, which demonstrates the ability of the model to cover the prestrain and temperature dependency of MS elastomer. Therefore, the expansion of the model to cover the prestrain and temperature enables the prediction of the mechanical performance of MS elastomer under various conditions and improves the possibilities for MS dampers and mounts to meet design criteria.